Integrative Analysis of RNA Expression and Regulatory Networks in Mice Liver Infected by Echinococcus multilocularis - Liu, Tingli; Li, Hong; Li, Yanping; Wang, Liqun; Chen, Guoliang; Pu, Guiting; Guo, Xiaola; Cho, William C.; Fasihi Harandi, Majid; Zheng, Yadong; Luo, Xuenong (Frontiers in Cell and Developmental Biology, 2022)
The larvae of Echinococcus multilocularis causes alveolar echinococcosis, which poses a great threat to the public health. However, the molecular mechanisms underlying the host and parasite interactions are still unclear. Exploring the transcriptomic maps of mRNA, miRNA and lncRNA expressed in the liver in response to E. multilocularis infection will help us to understand its pathogenesis. Using liver perfusion, different cell populations including the hepatic cells, hepatic stellate cells and Kupffer cells were isolated from mice interperitoneally inoculated with protoscoleces. Their transcriptional profiles including lncRNAs, miRNAs and mRNAs were done by RNA-seq. Among these cell populations, the most differentially-expressed (DE) mRNA, lncRNAs and miRNAs were annotated and may involve in the pathological processes, mainly including metabolic disorders, immune responses and liver fibrosis. Following the integrative analysis of 38 differentially-expressed DEmiRNAs and 8 DElncRNAs, the lncRNA-mRNA-miRNA networks were constructed, including F63-miR-223-3p-Fbxw7/ZFP36/map1b, F63-miR-27-5p-Tdrd6/Dip2c/Wdfy4 and IFNgAS1-IFN-γ. These results unveil the presence of several potential lncRNA-mRNA-miRNA axes during E. multilocularis infection, and further exploring of these axes may contribute to better understanding of the pathogenic mechanisms.